Dynamical Wave-Front Shaping and Extreme Nonreciprocity with Spatio-Temporal Modulated Metasurfaces - Cardin, Andrew E.; Silva, Sinhara R.; Vardeny, Shai. R.; Kort-Kamp, Wilton J. M.; Chen, Hou-Tong; Dalvit, Diego A. R.; Azad, Abul K.; Padilla, Willie (IEEE conference record-abstracts - IEEE International Conference on Plasma Science, 2020)
The control and manipulation of electromagnetic waves play a critical role in attaining enhanced performance of photonic systems. Spatio-temporal modulated metasurfaces (STMMs) - dynamic two-dimensional arrays of subwavelength resonators with arbitrary reflection amplitude and phase reconfigurability - have the potential to revolutionize fundamental and applied photonics by enabling arbitrary wave-front control. Although active metasurfaces have already been demonstrated through functional materials integration, they are still far from sufficient to realize fully reconfigurable functionalities. In this work, we experimentally demonstrate a spatio-temporal modulated reflectarray metasurface that is capable of dynamical wave-front shaping and nonreciprocal propagation of free space electromagnetic radiation. Arbitrary space-time phase distributions in reflection are achieved by embedding electronically modulated varactors into the resonators of our metasurface. Our experimental measurements reveal on-demand wave-front control of frequency conversion processes. We also demonstrate maximum violation of Lorentz reciprocity in both beam steering and focusing due to nonreciprocal excitation of surface plasmons. We developed an analytical generalized Bloch-Floquet theory valid for arbitrary two-dimensional spatial modulations. Our ultrathin and light-weight spatio-temporal modulated metasurface can enable novel functionalities in wireless communications, imaging, sensing, and nonreciprocal electromagnetic isolation.